(untitled) (Jóvenes en la Ciencia, 2024)
products such as personal care products. This increase in their demand and production has generated the accumulation of these nanomaterials in some environmental receptors, such as water; An example of this is the biological processes for wastewater treatment. That, is why in the present study the evaluation of the impact of cerium oxide nanoparticles in a biological system that used a microalgae-bacteria consortium for the removal of carbon, nitrogen and phosphorus, finding that there were no nanoparticles in the wastewater treatment process.